2016
DOI: 10.1016/j.cossms.2016.05.009
|View full text |Cite
|
Sign up to set email alerts
|

First-principles derived complexion diagrams for phase boundaries in doped cemented carbides

Abstract: This article reviews a method for calculating an equilibrium interfacial phase diagram depicting regions of stability for different interface structures as function of temperature and chemical potentials. Density functional theory (DFT) is used for interfacial energies, Monte Carlo simulations together with cluster expansions based on DFT results for obtaining configurational free energies, and CALPHAD-type modeling for describing the thermodynamic properties of the adjoining bulk phases. An explicit case, van… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“…When the first evidence of the presence of GB phase transformations appeared, these experimental findings are discussed in terms of transitions "pure (or dry) GB → few nanometer thin GBF → thick GB layer of bulk phase". Later, it has been shown that the variety of possible GB states (called complexions) is much richer (see for example References [17,[19][20][21][22][23][24][25][26][27]87,169,170]). One can imagine the transitions from clean GB to single-layer GBF, then to bi-layer, tri-layer etc.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…When the first evidence of the presence of GB phase transformations appeared, these experimental findings are discussed in terms of transitions "pure (or dry) GB → few nanometer thin GBF → thick GB layer of bulk phase". Later, it has been shown that the variety of possible GB states (called complexions) is much richer (see for example References [17,[19][20][21][22][23][24][25][26][27]87,169,170]). One can imagine the transitions from clean GB to single-layer GBF, then to bi-layer, tri-layer etc.…”
Section: Discussionmentioning
confidence: 99%
“…One can imagine the transitions from clean GB to single-layer GBF, then to bi-layer, tri-layer etc. [17,[19][20][21][22][23][24][25][26][27] Some of these transition lines can finish not only at the lines of bulk transitions but also in critical points in the middle of one-phase area of a bulk phase diagram [17,19,20,23,27,87].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations